Beyond the Basics: Investigating Grammar Struggles of Intermediate-Level University Learners - Najwa Suhartati; St Ayu Surayya; Laila Wati (Explorations in English Learning, 2026)
This study aims at identifying the grammar difficulties encountered by students in the Intermediate English Grammar course at Hamzanwadi University, investigate the contributing factors, and explore possible solutions proposed by students to address these challenges. Using a descriptive qualitative approach, the research involved 20 purposively selected students. The data were collected through questionnaire, interviews to obtain students’ perspectives and document analysis of their final examination papers to examine their actual grammar performance. To ensure the trustworthiness, methodological triangulation was applied. The data analysis in this study was carried out through three systematic stages, namely data reduction, data display, and conclusion drawing, which were integrated within the framework of triangulation. The results revealed that the most frequent grammatical difficulties were related to tenses and clauses, while additional challenges were observed in subject–verb agreement, modals, articles, and prepositions. These difficulties were largely attributed to limited practice opportunities, difficulty in memorizing grammar rules, restricted vocabulary, and less engaging teaching methods. To overcome these issues, it is suggested that students engage in more contextual grammar practice using authentic materials, while lecturers adopt more communicative and interactive teaching strategies supported by targeted remedial sessions and constructive feedback, in order to enhance students’ grammar mastery.